2020
DOI: 10.1111/cga.12389
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic changes in the cytoskeleton and adhesion apparatus during the conversion from pseudostratified single columnar to stratified squamous epithelium in the developing mouse esophagus

Abstract: The apico-basal (AB) polarity of epithelial cells is maintained by organized arrays of the cytoskeleton and adhesion apparatus. We previously reported that mouse embryonic esophageal epithelium exhibits interkinetic nuclear migration (INM), an AB-polarity-based regulatory mechanism of stem-cell proliferation, and suggested that the pseudostratified single columnar epithelium, a hallmark of INM, is converted to stratified squamous epithelium via rearrangement of the cytoskeleton and cell-adhesion apparatus. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Consistent with these results, recent studies showed that the maintenance of Wnt pathway at low level could facilitate the specification of anterior foregut endoderm toward the esophageal progenitor cells lineage[9, 31] while COL17A1 was required for skin keratinocyte stem cell maintenance[35]. High expression of COL17A1 was also identified as a marker of human esophageal quiescent stem/progenitor cells[5]. Hence, these results suggested that high levels of HD components and Wnt pathway negative regulators could sever as prominent markers of QBCs in the basal layer of the esophageal epithelium.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Consistent with these results, recent studies showed that the maintenance of Wnt pathway at low level could facilitate the specification of anterior foregut endoderm toward the esophageal progenitor cells lineage[9, 31] while COL17A1 was required for skin keratinocyte stem cell maintenance[35]. High expression of COL17A1 was also identified as a marker of human esophageal quiescent stem/progenitor cells[5]. Hence, these results suggested that high levels of HD components and Wnt pathway negative regulators could sever as prominent markers of QBCs in the basal layer of the esophageal epithelium.…”
Section: Resultsmentioning
confidence: 57%
“…As these organs are specified via a process of respiratoryesophageal separation (RES), the esophageal epithelium forms a simple columnar epithelium and then transforms into a stratified multi-layered epithelium [1][2][3][4]. The cellular and molecular mechanisms regulating RES and the esophageal epithelial morphogenesis during embryonic development have been extensively studied in recent years [2,[4][5][6][7][8][9]. However, it is less clear how the mature esophageal epithelium executes its self-renewal and maintenance of the proliferation-differentiation homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…The epithelia of the trachea and esophagus are not "simple" columnar but "pseudostratified" columnar, which is a hallmark of the epithelia in which the interkinetic nuclear migration (INM) works as a regulatory mechanism of epithelial proliferation and differentiation. 3 We further reported that transient and dynamic morphologic changes involving the cytoskeleton and cell-adhesion apparatus occur in the esophageal epithelium in close relation with the cessation of INM and transition into the stratified squamous structure. 3 INM is the apicobasal (AB) cell polarity-based oscillatory movement of epithelial cell nuclei that is synchronized with the progression of the cell cycle, that is, the M-phase at the apical surface and S-phase at the basal side, and thus generates the pseudostratified structure of the epithelium.…”
mentioning
confidence: 71%
“…3 We further reported that transient and dynamic morphologic changes involving the cytoskeleton and cell-adhesion apparatus occur in the esophageal epithelium in close relation with the cessation of INM and transition into the stratified squamous structure. 3 INM is the apicobasal (AB) cell polarity-based oscillatory movement of epithelial cell nuclei that is synchronized with the progression of the cell cycle, that is, the M-phase at the apical surface and S-phase at the basal side, and thus generates the pseudostratified structure of the epithelium. [4][5][6][7][8][9] It has been suggested that INM maximizes the number of mitoses at the limited apical surface to allow efficient stem/progenitor cell expansion.…”
mentioning
confidence: 71%
See 1 more Smart Citation